SUSTAINABILITY, ETHICAL CAPITAL, AND INVESTMENT BEHAVIOUR: EMPIRICAL EVIDENCE FROM ESG MUTUAL FUND PREFERENCES IN CULTURAL AND CREATIVE INDUSTRIES - Negi, Purnima; Srivastava, Dr. Mini (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The accelerated growth of the Environmental, Social, and Governance (ESG) investing has altered capital allocation trends, especially in cultural and creative industries (CCI) in which sustainability and ethical capital play a major role in investor sentiment. Nonetheless, there is a weak empirical research concerning the impact of sustainability perceptions and ethical orientation on ESG mutual fund choices in this industry. The fundamental issue in this study is that there is not quantitative knowledge on the drivers of behaviour in ESG investment choices among investors that are involved in CCI-related funds. The study incorporates a behavioural finance model that incorporates the sustainability consciousness, ethical capital perception, risk tolerance and expected return orientation. A questionnaire was given out to 420 retail and institutional investors in a structured form, and then it was empirically analyzed in terms of Structural Equation Modeling (SEM) and logistic regression. The findings indicate that sustainability awareness can have a positive impact on ESG mutual fund preference by 48 percentage points whereas perceived ethical capital can be used to determine investment likelihood by 37 percentage points. As compared to traditional motives of return maximization, which explain 18 percent of the decision variance, risk-adjusted expectations of returns explain 29 percent of the variance. Moreover, the demographic moderation analysis showed that the millennial investors have a preference of 52% higher in ESG allocation than other age groups do. The general model accounts 64 percent of variance in the selection behavior in ESG mutual funds. The results affirm the fact that sustainability-oriented ethical considerations are much more important than the pure financial aspects of investment decisions in the cultural and creative industries. These findings are empirical evidence in favour of the incorporation of ethical capital measures into the portfolio strategy planning and policy-making of sustainable development of finance.